PENGELOLAAN INSTAGRAM SEBAGAI MEDIA PROMOSI UNTUK MENINGKATKAN JUMLAH PELANGGAN PANIC ARTWORK - Karisma Putra, Abram Widya; Riyanto, Buddy; Siswanta, Siswanta (Solidaritas, 2024)
This research was motivated by the decreasing number of Panic Artwork customers. This can be seen from the lack of promotion carried out on Instagram. This research aims to provide a solution for using the Panic Artwork Instagram account as a promotional medium to increase the number of customers. This research uses a qualitative descriptive method with data collection techniques in the form of observation, interviews and documentation. The research results show that Panic Artwork effectively uses Instagram as a promotional medium through various features such as visual posts, reels and Instagram Ads, although the use of advertising is still limited. In addition, analysis using the AIDA theory (Attention, Interest, Desire, Action) shows that Instagram has succeeded in attracting audience attention, generating interest, creating desire, and encouraging purchasing actions through a consistent and interactive content strategy. However, this research also identified several factors that caused a decrease in the number of subscribers, such as a lack of promotional consistency and changes to the Instagram algorithm. These findings provide insight for Panic Artwork to further optimize the use of Instagram in an effort to increase the number of subscribers. Keywords: AIDA Theory,, Marketing Communication, Instagram, Panic Artwork, Social Media.